Artificial Intelligence and Cognitive Science 20th Irish Conference, AICS 2009, Dublin, Ireland, August 19-21, 2009, Revised Selected Papers - Coyle, Lorcan; Freyne, Jill (Lecture Notes in Artificial Intelligence, 2010)
This book constitutes the refereed proceedings of the 20th Irish Conference on Artificial Intelligence and Cognitive Science, AICS 2009, held in Dublin, Ireland in August 2009.  The  32 papers presented were carefully reviewed and selected for inclusion in the book. The topics covered are classification techniques, biologically-inspired computation, natural language processing, and applications of AI techniques for the social Web and financial markets.